Purchasing power parity: Granger causality tests for the yen-dollar exchange rate - Gunther Schnabl; Dirk Baur (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2001)
The paper analyses the causality between the Japanese-US relative export prices and the yen-dollar exchange rate. It explains why the Japanese yen proved strong even during the economic slump of the 1990s. The paper suggests that the appreciation of the Japanese yen forced the Japanese enterprises into price reductions and productivity increases, which put a floor under the high level of the yen and thus initiated rounds of appreciation. This corresponds to the conjecture of a vicious (virtuous) circle of appreciation and price adaptation.
urn:nbn:de:bsz:21-opus-24328
Keywords: 330; yen; yen-dollar exchange rate; purchasing power parity; Granger causality test; Wechselkurs; Kaufkraftparität; Außenhandelspreis; Exchange Rate Pass-Through; Yen; US-Dollar; Japan